2004
DOI: 10.1159/000082027
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in Young Adulthood: A Risk Factor for Pathological Gambling

Abstract: Background: Pathological gambling is more prevalent among postsecondary students than among the general adult population. While the prevalence of pathological gambling in this group has risen over the past decade, factors underlying the development of problem gambling among university students remain largely unexplored. One early study found alexithymia to be associated with pathological gambling. The aim of the present study was to further examine the relationship between alexithymia and gambling among postse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 51 publications
7
51
1
6
Order By: Relevance
“…2013 düzeyde kumar oynayanların oranı, aleksitimik olmayanlara göre daha yüksek bulunmuştur (Parker ve ark. 2005).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…2013 düzeyde kumar oynayanların oranı, aleksitimik olmayanlara göre daha yüksek bulunmuştur (Parker ve ark. 2005).…”
Section: Discussionunclassified
“…2009) gibi bozukluklarla sıkça birlikte görülebilen aleksitimik özelliklerin, bir davranışsal bağımlılık olan patolojik kumar oynama için de risk etmeni olabileceği düşünülebilir. Öte yandan, literatürde patolojik kumar oynama ve aleksitimi arasındaki ilişkiyi ele alan az sayıda çalışma bulunmaktadır (Lumley ve Roby 1995, Parker ve ark. 2005, Mitrovic ve Brown 2009, Toneatto ve ark.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…There is consistent evidence that alexithymia is elevated in people with eating disorders (Beales & Dolton, 2000;Carano et al, 2006;Cochrane, Brewerton, Wilson, & Hodges, 1993;De Panfilis, Salvatore, Avanzini, Gariboldi, & Maggini, 2001;Kessler, Schwarze, Filipic, Traue, & von Wietersheim, 2006;Mazzeo & Espelage, 2002;Pinaquy, Chabrol, Simon, Louvet, & Barbe, 2003;ZonneyvilleBender, van Goozen, Cohen-Kettenis, van Elburg, & van Engeland, 2002;Zonnevylle-Bender et al, 2004), problematic gambling (Lumley & Roby, 1995;Parker, Wood, Bond, & Shaughnessy, 2005), and alcohol and drug abuse or dependence (El Rasheed, 2001;Haviland, Hendryx, Shaw, & Henry, 1994;Kauhanen, Julkunen, & Salonen, 1992), although perhaps not cigarette smoking and nicotine dependence (Lumley, Downey, Stettner, Wehmer, & Pomerleau, 1994). One comprehensive study found that compared with controls, patients with eating disorders or alcohol-or drugrelated disorders had similar, high levels of alexithymia, and a path analysis suggested that alexithymia predicted depression that predicted the addictive behavior in these disorders (Speranza et al, 2004).…”
Section: Does Alexithymia Contribute To Unhealthy Behavior?mentioning
confidence: 99%
“…Ces taux de prévalence sont conformes, voire supérieurs, à ceux retrouvés dans la littérature [32]. Parker et al [35] ont, quant à eux, trouvé une prévalence inférieure dans leur échantillon. D'une part, il est possible que les résultats de ces recherches aient été différents si un diagnostic de jeu pathologique avait été posé (utilisation de critères diagnostiques valides en plus du SOGS).…”
Section: Scores D'alexithymieunclassified